Work Ethic as the Foundation of Organizational Commitment - Fajri Al Farikhi; Awang Setiawan Wicaksono (Psikostudia : Jurnal Psikologi, 2024)
Work ethics play a central role in determining the level of productivity and success of individuals in an organization. Modern work demands influenced by technological developments and globalization increasingly emphasize the importance of work ethics. Individuals who have a strong work ethic focus not only on completing their tasks, but also on how they can contribute long-term to the success of the organization. The aim of this research is to determine the relationship between organizational commitment and work ethics among PT X employees. This research method uses quantitative with a correlation approach. The subject of this research were PT X employees, consisting of 105 respondents. Based on the research results it was found that. Organizational commitment and work ethics do not have a simultaneous relationship but have a partial relationship from the aspects of assertive commitment and normative commitment to work ethic. The implication of this research is that development is needed in smaller aspects to create a good work ethic in an organization.Etos kerja memainkan peran sentral dalam menentukan tingkat produktivitas dan keberhasilan individu dalam suatu organisasi. Tuntutan kerja modern yang dipengaruhi oleh perkembangan teknologi dan globalisasi semakin menekankan pentingnya etos kerja. Individu yang memiliki etos kerja kuat tidak hanya fokus pada penyelesaian tugas-tugas karyawan, tetapi juga pada bagaimana karyawan dapat memberikan kontribusi jangka panjang bagi kesuksesan organisasi. Tujuan dari penelitian ini adalah untuk mengetahui Hubungan komitmen Organisasi dan Etos Kerja Pada Karyawan PT X. Metode Penelitian ini menggunakan Kuantitatif dengan pendekatan korelasi. Subjek penelitian ini adalah karyawan PT X yang terdiri dari 105 responden. Berdasarkan hasil penelitian ditemukan bahwa. Komitmen organisasi dan etos kerja tidak memiliki hubungan secara simultan, namun memiliki hubungan yang parsial dari aspek komitmen asertif dan komitmen normatif terhadap etos kerja. Implikasi dari penelitian ini yaitu diperlukannya pengembangan dalam aspek yang lebih kecil untuk mewujudkan etos kerja yang baik pada suatu organisasi.